Performance of Sahiwal-friesian cows under grazing and stallfeedings management - D., Soetrisno; M., Mahyuddin; P., Vijchulata; A., Osman; Tan , H. S. (1985)
Ten Sahiwal-friesian first lactating cows were divided randomly into 2 groups to detrmine the effect of grazing and stallfeeding management on their performance. Following the split-plot intime design, it is observed that period of lactation significantly affected the average total milk production (P < 0.01) and body weight change (P < 0.05). There were also significant (P < 0.05) effects of interaction between lactation period and block, and between lactation period and block, and between lactation period and feeding systems on the average total milk production. Milk yield declined as the lactation pregressed except for the grazing cows during the first five month of study, where increase of about 1.8% in milk yield was observed. During the 8 months study period grazed and stallfed cows produced 10,203.6 kg and 8,134.5 kg of milk, respectively. No significant differences between the treatment groups in length of calving to first estrus (60.8 days vs 86.8 days), conception rate (3.0 vs 3.6), length of calving to cenception (131.8 days vs 171.4 days), calving interval (409.2 days vs 447.8 days) and birth weight of calves (26.6 kg vs 29.4 kg). It is concluded that grazing cows tend to produce more milk and obtain slightly better reproductive performance than stallfed cows.